Scarlet fever on the background of toxicodermia in a child: case report and mini-review - S. Nykytyuk; O. Mochulska; S. Levenets; T. Vorontsova (Zaslavsky O.Yu., 2021)
The article presents a case of scarlet fever on the background of toxicodermia in a 12-year-old girl. The disease most probably developed in response to a combination of etiological factors such as bacterial infection and allergic reaction to exotoxins. The clinical picture was dubious, involving mucous membranes of the nose, mouth, and skin. Parenteral administration of glucocorticoids, antihistamines, detoxification, antibiotic therapy, and topical treatment led to rapid regression of clinical symptoms and prevented the development of complications. Sometimes, it is difficult to determine the etiology of toxicodermia combined with scarlet fever. Physicians should examine all patients with allergodermatoses for the presence of beta-hemolytic streptococcus and antibodies.